Quality of Judo World Championships in relation to justice theories and behavior - A case study of the 2017 World Judo Championships in Budapest - Zimányi, R. G.; Géczi, G. (International Journal of Wrestling Science, 2018)
The judo world championships are major sport events, where, as in any other area of life, we strive for justice. How can the competitor`s list of judo world championships be evaluated as just? When is the seeding right? When can we talk about a fair draw? When is a competition system fair? How can the final result be just and fair? Does everyone think that the final result is just? To answer the questions correctly, first of all we need to clarify the telos of the specific sporting event. This study presents the justice theories and examines the evolutionist conceptions from Aristotle's justice theory, through meritocracy and egalitarianism, to positive discrimination. It analyses a sporting event, the World Judo Championships 2017, held in Budapest. In the study we examine the competitor`s list, the seeding, the draw, the competition systems and the final results of this judo world championship. Parallel to the analysis of justice theories, we use the method of personal observation as well. The study is based on an interview with the Operational Director of the Hungarian Judo Federation. We conclude that many theories of justice appear in relation to the judo world championships. However, only those theories of justice can be accepted which are consistent with the telos, the ultimate object or aim, of the event. As a summary the competitor`s list, the seeding, the draws, the competition system and the final result can be fair, but their acceptance depends on which theory of justice is applied. The research confirms that there are such theories of justice which do not meet the telos.